2022
DOI: 10.1111/issj.12338
|View full text |Cite
|
Sign up to set email alerts
|

Validating nature relatedness scale in the Philippines: Social responsibility as a cultural driver on why nature relatedness promotes green purchase intention

Abstract: Despite the global nature of environmental problems, research on environmental psychology has been mainly based on Western countries, and very limited studies looked into environmental psychological constructs and processes through a non‐Western cultural lens. The present study examined the psychometric properties of the short‐form Nature Relatedness Scale (NR‐6) and investigated culturally relevant mechanisms that facilitate the positive influence of nature relatedness on green purchase intentions among Filip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…In particular, the aspects of nature relatedness reflecting an enjoyment of nature were significantly associated with reduced ill health, while the aspects of nature relatedness reflecting self-identification with nature were associated with increased depression, anxiety, or stress, after accounting for potential confounding factors. More recently, Aruta and Pakingan [34] tested the validity of nature relatedness in a different cultural context (i.e., Philippines) and found a positive association with green purchase intentions.…”
Section: Exploring the Evolution Of The Connection To Nature Conceptu...mentioning
confidence: 99%
“…In particular, the aspects of nature relatedness reflecting an enjoyment of nature were significantly associated with reduced ill health, while the aspects of nature relatedness reflecting self-identification with nature were associated with increased depression, anxiety, or stress, after accounting for potential confounding factors. More recently, Aruta and Pakingan [34] tested the validity of nature relatedness in a different cultural context (i.e., Philippines) and found a positive association with green purchase intentions.…”
Section: Exploring the Evolution Of The Connection To Nature Conceptu...mentioning
confidence: 99%
“…A possible explanation is that people high in Humanism and Kantianism view the world from a larger scheme of things which allows them to engage in actions that promote the welfare of people and other beings beyond themselves. Previous studies showed that people who view the world from a wider perspective tend to be more affiliated with the natural world and engage more in ecological behaviors (Aruta, 2021a, 2021b, 2021c, 2022a, 2022b; Aruta & Pakingan, 2022; Passmore & Howell, 2014). This present finding extended this line of research not only by confirming that Light Triad traits could motivate environmental concern and intentions but also by demonstrating that environmental concern was a viable psychological mechanism that can link the Light Triad traits and people’s willingness to purchase products that cause less damage to the natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…The participants rated each statement on a 7-point Likert scale ranging from 1 = strongly disagree to 7 = strongly agree , with higher scores indicating greater levels of green purchase intentions. Past studies used these items to assess green purchase intentions using Filipino samples (Aruta, 2021b; Aruta & Pakingan, 2022). Participants’ scores yielded a reliability of α = .88 and ω = .88.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, initial studies have focused on the psychometric examination of Western‐developed measures of nature relatedness (see Aruta, 2021a), and its importance in promoting pro‐environmental behaviours and well‐being in Filipinos (Aruta, 2021b, 2021c). Moreover, emerging findings found that science literacy (Aruta, 2022c), personal experience of climate change, climate anxiety (Simon et al, 2022), environmental attitudes (Aruta, 2021b), social responsibility (Aruta & Paceño, 2022; Aruta & Pakingan, 2022), norms (Aruta, 2022a, 2022b) and perceived behavioural control (Aruta, 2022b) can motivate pro‐environmental behaviours (e.g., reducing plastic use and green purchasing) and behavioural engagement to climate change (e.g., household energy conservation). On the other hand, materialist values were found to be associated with poorer pro‐environmental behaviours (Aruta, 2021b; Aruta & Ballada, 2022) and well‐being in Filipinos (Aruta, 2021c).…”
Section: Environmental Psychology Studies In the Philippinesmentioning
confidence: 99%